A Novel Triple-Fluorescent HCMV Strain Reveals Gene Expression Dynamics and Anti-Herpesviral Drug Mechanisms - Rand, Ulfert; Kubsch, Tobias; Kasmapour, Bahram; Cicin-Sain, Luka (Frontiers in Cellular and Infection Microbiology, 2021)
Human Cytomegalovirus (HCMV) infection may result in severe outcomes in immunocompromised individuals such as AIDS patients, transplant recipients, and neonates. To date, no vaccines are available and there are only few drugs for anti-HCMV therapy. Adverse effects and the continuous emergence of drug-resistance strains require the identification of new drug candidates in the near future. Identification and characterization of such compounds and biological factors requires sensitive and reliable detection techniques of HCMV infection, gene expression and spread. In this work, we present and validate a novel concept for multi-reporter herpesviruses, identified through iterative testing of minimally invasive mutations. We integrated up to three fluorescence reporter genes into replication-competent HCMV strains, generating reporter HCMVs that allow the visualization of replication cycle stages of HCMV, namely the immediate early (IE), early (E) and late (L) phase. Fluorescent proteins with clearly distinguishable emission spectra were linked by 2A peptides to essential viral genes, allowing bicistronic expression of the viral and the fluorescent protein without major effects on viral fitness. By using this triple color reporter HCMV, we monitored gene expression dynamics of the IE, E and L genes by measuring the fluorescent signal of the viral gene-associated fluorophores within infected cell populations and at high temporal resolution. We demonstrate distinct inhibitory profiles of foscarnet, fomivirsen, phosphonoacetic acid, ganciclovir and letermovir reflecting their mode-of-action. In conclusion, our data argues that this experimental approach allows the identification and characterization of new drug candidates in a single step.